Implementation Of The Pancasila Profile Project And The Use Of Learning Media In The Independent Learning Curriculum - Muhammad Arif; Veni; Andri Yanto (Cv. Kilau Rashdan Publishing, 2026)
The strengthening project of the Pancasila profile is a learning activity that must be implemented within the independent learning curriculum. Additionally, specifically for IPAS (Natural and Social Sciences) learning, which fundamentally examines natural and social phenomena, learning media is crucial to support the achievement of learning objectives. The aim of this research is to identify the implementation of the Pancasila student profile strengthening project and the use of learning media in IPAS subjects. This research is a survey using a questionnaire as the instrument. The respondents in this study are elementary school teachers who have implemented the independent learning curriculum. The research data were analyzed descriptively with the help of graphs. The results of this study indicate that training on the independent learning curriculum is needed to help teachers understand and implement the Pancasila profile strengthening project. Difficulties faced by teachers in implementing this project include time constraints, inadequate facilities, passive students, and difficulties in creating project modules. The learning media most commonly used by teachers in IPAS teaching are visual aids, but ICT media have the potential to be used based on considerations of ICT facilities and the teachers' ability to operate ICT for learning purposes